Peran Media Sosial dalam Strategi Digital Marketing: Tinjauan Sistematis terhadap Pengaruhnya di Pasar Indonesia - Akbarona, Danang Aziz; Intan, Lusi Reni; Triana, Ade; Dila, Fara (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This-study aims-to examine the-role of socialmedia in digital marketing strategies in Indonesia through a Systematic Literature Review (SLR) with a qualitative approach, focusing on its impact on brand mindfulness, client engagement, brand fidelity, and the marketing performance of micro, small,and medium enterprises(MSMEs). By reviewing literature from academic journals, conference papers, and scholarly publications, this study identifies crucial themes, including the effectiveness of social media platforms like Instagram and Twitter in enhancing brand mindfulness and deals, the role of influencer marketing in strengthening marketing strategies, and the positive impact of social media on MSMEs. Success factors include the quality of applicable and engaging content, active commerce with cult, and the use of analytics to measure crusade effectiveness, while major challenges encompass violent competition, resource limitations for MSMEs, and changes in platform algorithms. The study recommends training in content operation, integrating influencer marketing with organic content, and using analytics to optimize marketing strategies. Limitations include the focus on English and Indonesian literature and confined access to paid journals, suggesting unborn exploration to explore platforms like TikTok and the impact of algorithm changes